Perlindungan Hukum Pemegang Hak Cipta Atas Karya Video Youtube Yang Di Unggah Ulang Di Tiktok Oleh Pihak Lain - Adam Putra Hidayat, Mohamad; Anggriani, Reni (Magister Kenotariatan, Universitas Jambi, 2025)
This research discusses legal protection for YouTube video works that are re-uploaded on TikTok without the permission of the copyright holder. The phenomenon of digital content re-uploading has become increasingly prevalent as social media platforms develop into sources of both entertainment and income. The research employs a normative legal method, examining statutory regulations, doctrines, and policies related to copyright law. The findings indicate that re-uploading YouTube content to TikTok may constitute copyright infringement if it exceeds the limits of fair use and causes harm to the copyright holder. Legal protection is provided through preventive measures—such as regulations, government supervision, platform policies, and public awareness—and repressive measures in the form of dispute resolution through both litigation and non-litigation mechanisms. Therefore, collaboration among the government, digital service providers, and the public is essential to ensure legal certainty while safeguarding the moral and economic rights of copyright holders.